1999
DOI: 10.1002/(sici)1522-9505(19991101)271:1<1::aid-apmc1>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion-precipitation polymerization of diisopropyl fumarate

Abstract: The emulsion polymerization of diisopropyl fumarate initiated with a redox initiator and an anionic emulsifier was investigated. The study includes conversion and particle number determinations as a function of time, temperature and the concentrations of initiator, emulsifier and monomer. The reaction is characterized by a limiting conversion following a linear increase of the conversion with time from the beginning on. The reaction rate is very much higher than those obtained in bulk or in solution polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was reported that the propagation and termination rate constants of DRF ( k p = 0.058–0.68 L/mol s and k t = 26–560 L/mol s) were much smaller than the values for conventional vinyl monomers (typically, k p = 10 2 –10 4 L/mol s and k t = 10 6 –10 8 L/mol s) . (j) The produced PDRFs exhibited unique properties from the viewpoints of both fundamental researches and industrial applications; for example, polymerization kinetics, reaction mechanism, reaction processes, copolymerization, functional polymer syntheses, thermal degradation, tacticity, solution property, solid‐state dynamic, mechanical property, thin film and surface properties, gas permeation, liquid crystals, electronic property, electro‐optical property, optical property, and optical materials application . Recently, various approaches for controlled polymer synthesis and materials design using living radical polymerization techniques have been reported, but no report on the living radical polymerization of DRF is seen in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the propagation and termination rate constants of DRF ( k p = 0.058–0.68 L/mol s and k t = 26–560 L/mol s) were much smaller than the values for conventional vinyl monomers (typically, k p = 10 2 –10 4 L/mol s and k t = 10 6 –10 8 L/mol s) . (j) The produced PDRFs exhibited unique properties from the viewpoints of both fundamental researches and industrial applications; for example, polymerization kinetics, reaction mechanism, reaction processes, copolymerization, functional polymer syntheses, thermal degradation, tacticity, solution property, solid‐state dynamic, mechanical property, thin film and surface properties, gas permeation, liquid crystals, electronic property, electro‐optical property, optical property, and optical materials application . Recently, various approaches for controlled polymer synthesis and materials design using living radical polymerization techniques have been reported, but no report on the living radical polymerization of DRF is seen in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Other polymerization methodologies have been researched, with the aim of achieving reaction rates comparable to those of other vinyl or acrylic monomers. Thus, the emulsion polymerization of diisopropyl fumarate (DIPF) using a redox initiator was studied [16]. It was found that the reaction rate was very much higher than those obtained in bulk or solution polymerization; although at short times (20 min) a limit conversion was reached.…”
Section: Synthesis Of Homo-and Copolymersmentioning
confidence: 99%
“…[ 503 ] The rate of polymerization of D i PrFm could be increased by an emulsion polymerization process in water. [ 504 ] Poly(DEFm) could also be obtained in water by complexing the monomer with cyclodextrin. [ 505,506 ] Microwave initiation also proved to be faster than thermal initiation for poly(D i PrFm) formation.…”
Section: Polymerization Of (Meth)acrylic Monomers and Analogsmentioning
confidence: 99%